Confined glassy dynamics at grain boundaries in colloidal crystals - Nagamanasa, K. Hima (National Academy of Sciences, 2011)
Grain boundary (GB) microstructure and dynamics dictate the macroscopic properties of polycrystalline materials. Although GBs have been investigated extensively in conventional materials, it is only recently that molecular dynamics simulations have shown that GBs exhibit features similar to those of glass-forming liquids. However, current simulation techniques to probe GBs are limited to temperatures and driving forces much higher than those typically encountered in atomic experiments. Further, the short spatial and temporal scales in atomic systems preclude direct experimental access to GB dynamics. Here, we have used confocal microscopy to investigate the dynamics of high misorientation angle GBs in a three-dimensional colloidal polycrystal, with single-particle resolution, in the zero-driving force limit. We show quantitatively that glassy behavior is inherent to GBs as exemplified by the slowing down of particle dynamics due to transient cages formed by their nearest neighbors, non-Gaussian probability distribution of particle displacements and string-like cooperative rearrangements of particles. Remarkably, geometric confinement of the GB region by adjacent crystallites decreases with the misorientation angle and results in an increase in the size of cooperatively rearranging regions and hence the fragility of the glassy GBs.